The disaster recovery handbook a step-by-step plan to ensure business continuity and protect vital operations, facilities, and assets - Wallace, Michael, 1960- (AMACOM ; McGraw-Hill [distributor], 2011)
No organization is safe without a disaster recovery plan in place. Expanded and up to date, this is the ultimate resource.
"This CD-ROM contains the forms from the book. The files on this CD-ROM are in Microsoft Word, Microsoft Excel, and Microsoft Project. In order to read these files, you will need Microsoft Word 6.0 or higher, Microsoft Excel 2007 or higher, and Microsoft Project 2007 or higher."--Disc label.
Some online versions lack accompanying media packaged with the printed version.
Keywords: Emergency management -- Handbooks, manuals, etc.; Crisis management -- Handbooks, manuals, etc.; Computer security -- Handbooks, manuals, etc.; Data protection -- Handbooks, manuals, etc.; Data recovery (Computer science) -- Handbooks, manuals, etc.; Business planning -- Handbooks, manuals, etc.; elektronické knihy; electronic books